As normativas internacionais de direitos humanos na fundação do estado de Israel e o conflito Israel-Palestina - Puosso, Desirée Garção (2021)
It is necessary to expose ex ante the purpose of this scientific work, which aims through technical knowledge to discuss the importance of the most primary guarantees present in the dimensions of human rights, which may be applied to the object of the study under analysis. In order to examine these guarantees, it is first necessary to understand – in a technical manner and never in a binary or manicheistic way – the narratives of the two diasporic peoples, which are Jews and Palestinians, that culminated in the need of the formost to claim a homeland, and in the struggle of the latter to maintain themselves in a territory, and finally, to be recognized as a nation state. This research seeks to inform that there are two diasporic narratives in confrontation and conflicting national wills, marked by the tragedy of the deterritorialization of both peoples, which weighs in different historical moments. The issue must be understood from the point of view of cultural human rights, bringing the debate to current topics such as globalization, multiculturalism, miscegenation and cultural, ethnic and religious coexistence. Therefore, the present proposes to clarify what Zionism is in fact and what its origin is from that to understand its connection with the right to nationality, a guarantee envisaged in the Universal Declaration of Human Rights, and which was proclaimed on December 10, 1948, by the General Assembly of the United Nations, that is, in the same year of the foundation of the State of Israel. It should be noted that, contrary to what some have understood in recent decades, Zionism dates back to the nineteenth century and is much more related to the Jewish diaspora as a whole than to the Second World War. 10 As well, it is intended to demonstrate that the Zionist movement is guided by the principle of self-determination of peoples and, finally, to clarify the obligation of the State of Israel to obey the principles of equality between States and the peaceful solution of conflicts, which are found as some of the purposes of the United Nations, including being provided in the Charter of the United Nations. Explaining, therefore, the tradition of Brazilian diplomacy understanding in relation to this conflict. In view of this, explanations of the conflict will be brought, which will be reduced to focus on the genesis of the dispute between Jews and Arabs living in Palestine. It is evident, after all, to combat the misinformation present in post-truth times, which makes the discussion about the complex issue now addressed in academic forums crucial, i.e., in an environment open to diverse opinions and that demands scientific knowledge. The present work can contribute to the debate about Zionism(s) and anti-Semitism